The phenotypic spectrum of organic acidurias and urea cycle disorders. Part 2: the evolving clinical phenotype. Issue 6 (15th April 2015) - Kölker, Stefan; Valayannopoulos, Vassili; Burlina, Alberto B.; Sykut‐Cegielska, Jolanta; Wijburg, Frits A.; Teles, Elisa Leão; Zeman, Jiri; Dionisi‐Vici, Carlo; Barić, Ivo; Karall, Daniela; Arnoux, Jean‐Baptiste; Avram, Paula; et al.
Abstract: Background: The disease course and long‐term outcome of patients with organic acidurias (OAD) and urea cycle disorders (UCD) are incompletely understood. Aims: To evaluate the complex clinical phenotype of OAD and UCD patients at different ages. Results: Acquired microcephaly and movement disorders were common in OAD and UCD highlighting that the brain is the major organ involved in these diseases. Cardiomyopathy [methylmalonic (MMA) and propionic aciduria (PA)], prolonged QTc interval (PA), optic nerve atrophy [MMA, isovaleric aciduria (IVA)], pancytopenia (PA), and macrocephaly [glutaric aciduria type 1 (GA1)] were exclusively found in OAD patients, whereas hepatic involvement was more frequent in UCD patients, in particular in argininosuccinate lyase (ASL) deficiency. Chronic renal failure was often found in MMA, with highest frequency in mut 0 patients. Unexpectedly, chronic renal failure was also observed in adolescent and adult patients with GA1 and ASL deficiency. It had a similar frequency in patients with or without a movement disorder suggesting different pathophysiology. Thirteen patients (classic OAD: 3, UCD: 10) died during the study interval, ten of them during the initial metabolic crisis in the newborn period. Male patients with late‐onset ornithine transcarbamylase deficiency were presumably overrepresented in the study population. Conclusions: Neurologic impairment is common in OAD and UCD, whereas the involvement of other organs (heart, liver, kidneys, eyes) follows a disease‐specific pattern. The identification of unexpected chronic renal failure in GA1 and ASL deficiency emphasizes the importance of a systematic follow‐up in patients with rare diseases.